Interactive Worksheet to Improve Children's Literacy Ability : Worksheet Interaktif untuk Meningkatkan Kemampuan Literasi Anak - Ryan Humardani Syam Pratomo; Sri Mukminati Nur; Alin Liana; Sulfaidah Sulfaidah; Khadijah Khadijah; Maisya Zahra Al-Banna (Yayasan Ahmar Cendekia Indonesia, 2022)
The holiday in the month of Ramadan makes some parents confused about how to keep their children studying even though they are fasting. Where children sometimes only play gadgets which ultimately have no benefit for them. So, we held an activity with the theme “Interactive Worksheet to Improve Children's Literacy Ability. The purpose of this activity is for children to be able to improve children's literacy skills regarding the meaning of the holy month of Ramadan by using worksheets and increase children's activity in knowing the meaning of the month of Ramadan. One type of learning media or learning aids is student worksheets or also called worksheets. The formulation of the problem from this activity is; (1) How to improve children's literacy skills in knowing the meaning of the month of Ramadan? (2) How to increase children's activity in knowing the meaning of the month of Ramadan in using worksheets? This activity is carried out during the month of Ramadan 1443H, which is April 3 – May 2, 2022. The participants of the activity are all Indonesian children aged 5-10 years, who are committed to learning Ramadan knowledge with parental assistance. The results of this activity are from 19 participants, there are 14 participants who get the Excellent category with a score of 97% and 100%. The percentage of participants who were able to achieve the Excellent category was 74%, or most of the participants were able to follow well the entire series of Ramadan literacy activities. Students get the Deficient category are from 19 participants, there were 5 participants who got the Deficient category. The percentage of participants who get the Deficient category is 26% or a small percentage of participants are less able to take part in Ramadan literacy activities. Abstrak Libur pada bulan Ramadan membuat beberapa orang tua bingung bagaimana cara agar anak-anak mereka tetap belajar meskipun sedang berpuasa. Dimana anak-anak terkadang hanya bermain gadget yang akhirnya tidak memiliki manfaat bagi mereka. Sehingga kami mengadakan kegiatan yang bertema “Worksheet Interaktif untuk Meningkatkan Kemampuan Literasi Anak. Tujuan dari kegiatan ini yaitu agar anak-anak mampu meningkatkan kemampuan literasi anak mengenai makna dari bulan suci Ramadan dengan menggunakan worksheet dan meningkatan keaktifan anak dalam mengetahui makna bulan Ramadan. Salah satu jenis media pembelajaran atau alat bantu pembelajaran adalah lembar kerja siswa atau disebut juga worksheet. Adapun rumusan masalah dari kegiatan ini adalah: (1) Bagaimana meningkatkan kemampuan literasi anak dalam mengetahui makna bulan Ramadan? (2) Bagaimana meningkatkan keaktifan anak dalam mengetahui makna bulan Ramadan dalam menggunakan worksheet? Kegiatan ini dilaksanakan selama bulan Ramadan 1443H, yaitu 3 April – 2 Mei 2022. Peserta kegiatan adalah seluruh anak Indonesia berusia 5-10 tahun, yang berkomintmen untuk belajar ilmu Ramadan dengan pendampingan orang tua. Hasil kegiatan ini yaitu adalah dari 19 peserta, terdapat 14 peserta yang mendapatkan kategori Excellent dengan nilai 97% dan 100%. Persentase peserta yang mampu meraih kategori Excellent yaitu 74%, atau sebagian besar peserta mampu mengikuti dengan baik seluruh rangkaian kegiatan Literasi Ramadan. Siswa yang mendapatkan kategori Deficient yaitu dari 19 peserta, terdapat 5 orang peserta yang mendapatkan kategori Deficient. Persentase peserta yang mendapatkan kategori Deficient yaitu 26% atau sebagian kecil peserta kurang mampu mengikuti kegiatan Literasi Ramadan